Techno-Economic Analysis for Bioethanol Plant with Multi Lignocellulosic Feedstocks - Penjit Srinophakun; Anusith Thanapimmetha; Thongchai Rohitatisha Srinophakun; Pramuk Parakulsuksatid; Chularat Sakdaronnarong; Monsikan Vilaipan; Maythee Saisriyoot (International Journal of Renewable Energy Development, 2020)
Oil palm empty fruit bunch and trunk are classified as primary lignocellulosic residues from the palm oil industry. They are considered to be promising feedstocks for bioconversion into value-added products such as bioethanol. However,using these lignocellulosic materials to produce bioethanol remains a significant challenge for small and medium enterprises. Hence, techno-economic and sensitivity analyses of bioethanol plant simultaneously treating these materials were performed in this study. The information based on preliminary experimental data in batch operations wasemployed to develop a simulation of an industrial-scale semi-continuous production process. Calculations of mass balance, equipment sizes, and production cost estimation of the production plant of various capacities ranging from 10,000 L/day to 35,000 L/day were summarized. The result based on 20 years of operation indicated that the net present value of theplant of lower capacities was negative. However,thisvalue became positive when the plant operated with a higher capacity, 35,000 L/day.The highest ethanol yield, 294.84 LEtOH/tonfeedstock, was produced when the planttreated only an empty fruit bunch generating 8.94% internal rate of return and US$0.54 production cost per unit.Moreover, the higher oil palm trunk ratio in the feedstock, the lower ethanol yield contributing to the higher production cost per unit.